Understanding and targeting resistance mechanisms in NSCLC - Rotow, Julia; Bivona, Trever G. (Nature reviews. Cancer, 2017)
Key Points The spectrum of known and putative oncogenic drivers with companion targeted therapies continues to increase. As broader mutational testing becomes more clinically available, a greater proportion of patients with non-small-cell lung cancer (NSCLC) will be eligible for targeted therapies. Mechanisms of resistance to targeted therapies can be divided into 'on-target' alterations in the primary drug target and 'off-target' changes that influence downstream and parallel bypass signalling pathways. There is both signalling crosstalk and overlap among downstream and bypass signalling pathways that lead to resistance to the different targeted therapies currently in clinical use for treating NSCLC, suggesting that common themes in the development of drug resistance can be leveraged to guide further development of therapeutic agents and strategies. The upfront combination of therapies targeting both the oncogenic driver and common bypass pathways might delay the onset of disease progression in NSCLC and is the subject of ongoing clinical trials. Bidirectional signalling between tumour cells and components of the tumour microenvironment (TME) shapes both the characteristics of the TME and the propensity of a tumour cell towards therapeutic resistance. Tissue biopsy at disease progression might identify modes of therapeutic resistance to guide the rational selection of subsequent lines of therapy. Serial assessment of circulating tumour DNA might provide a complementary approach to capture heterogeneous and evolving resistance mechanisms in patients. Despite advances in targeting oncogenic driver mutations, advanced-stage non-small-cell lung cancer (NSCLC) remains largely incurable due to therapeutic resistance. This Review focuses on how understanding the mechanisms of resistance to targeted therapies in NSCLC can inform improved treatment strategies. The expanding spectrum of both established and candidate oncogenic driver mutations identified in non-small-cell lung cancer (NSCLC), coupled with the increasing number of clinically available signal transduction pathway inhibitors targeting these driver mutations, offers a tremendous opportunity to enhance patient outcomes. Despite these molecular advances, advanced-stage NSCLC remains largely incurable due to therapeutic resistance. In this Review, we discuss alterations in the targeted oncogene ('on-target' resistance) and in other downstream and parallel pathways ('off-target' resistance) leading to resistance to targeted therapies in NSCLC, and we provide an overview of the current understanding of the bidirectional interactions with the tumour microenvironment that promote therapeutic resistance. We highlight common mechanistic themes underpinning resistance to targeted therapies that are shared by NSCLC subtypes, including those with oncogenic alterations in epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK), ROS1 proto-oncogene receptor tyrosine kinase (ROS1), serine/threonine-protein kinase b-raf (BRAF) and other less established oncoproteins. Finally, we discuss how understanding these themes can inform therapeutic strategies, including combination therapy approaches, and overcome the challenge of tumour heterogeneity.